La Loi constitutionnelle de 1982. Droit des autochtones - O’Reilly, James (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
This article deals with the rights of the Aboriginal Peoples of Canada recently recognized in the Constitution Act, 1982. It provides a brief analysis of the nature and scope of these rights and their historical context by reference to some of the principal cases on Indian title. There is a short treatment of section 91(24) of the Constitution Act, 1867, and finally a summary of the 1983 Constitutional Accord on Aboriginal Rights and the amendments to the Constitution of Canada contemplated by the Accord.